(untitled) (Italian Journal of Public Health, 2009)
Background: Fundamental political changes in Central and South Eastern Europe in the aftermath of the fall of the iron curtain enter a new phase after accession of some countries to the EU. Methods: The article reviews and analyses current regional and international developments and factors, which are influential for health policies in the region. Special attention is given to collaboration – both of technical and of political nature – within the region and with international organizations and donors. The response to international health policy frameworks and the impact of international health strategies is being analysed. Results: The results point towards common political and structural features in the countries of the region. Regional networks seem to be a very promising structure for health policy development. Despite the political will, health care reforms still don’t show the expected results. The partnership with the EU is the most influential one. Conclusions: Regional networks need to be transformed into regionally owned structures. It seems to be crucial to tackle informal parallel systems and to increase responsibility for health professionals. The need for reforms and the prospect of neighbouring and joining the EU create a unique momentum to develop own health policies without international interference.